An Alternative Therapy for Recurrent Stasis Ulcers in Chronic Venous Insufficiency: Venocuff - Celal Yavuz; Sinan Demirtas; Orkut Guclu; Oguz Karahan; Suleyman Yazici; Ahmet Caliskan; Binali Mavitas (Case Reports in Vascular Medicine)
Chronic venous insufficiency may cause stasis ulcers that significantly impact on the quality of life. Many methods have been described for preventing or treating these ulcers. However, stasis ulcers often recur as a result of continuing venous insufficiency. Here we report a 30-year-old male patient with chronic venous insufficiency. He was admitted to the hospital owing to recurrent stasis ulcers. He had a history of various flavonoid drug usage and compression therapies over the previous six years. Venous Doppler sonography revealed combined saphenofemoral and deep femoral venous insufficiency. Venocuff was applied to the prejunctional and postjunctional parts of the femoral vein and the saphenofemoral junction. The patient was discharged on the postoperative second day, and a low-molecular-weight heparin dressing composed of calcium alginate was applied to the ulcer wound for one week after the operation. The stasis ulcer wound was totally healed after one month. The patient was followed up six months after the operation, and no postoperative complications or new ulceration was observed. Recurrent stasis ulcers are major reasons for hospitalization in patients with chronic venous insufficiency. Venocuff application for reducing venous insufficiency may be a good option for adjunctive ulcer therapy and for preventing recurrences of the problem.